Stanovení pracovního rozsahu a účinnosti vodního trkače - Růžička, Jakub (Vysoké učení technické v Brně. Fakulta stavební, 2019)
Tato práce stanovuje pracovní rozsah a účinnosti vodního trakače experimentálním měřením v laboratoři. Měření probíhá na třech odlišných dimenzích vodního trkače, které navrhnul a sestavil autor této práce. Zde se také zjišťuje, zdali má závaží na tepacím ventilu vliv na účinnost trkače. Dále se zabývá porovnáváním dosavadních způsobů dopravy vody na táborech oproti výhodám trkače. Princip vodního trkače vychází z hydraulického rázu, který je zde důkladně rozepsán. Obsahem jedné z kapitol je návod na umístění vodního trkače na tok a jeho kompletní zapojení. Jelikož do trkače společně s vodou mohou být dopravovány nečistoty, tak se práce zaměřuje na přidání vtokového objektu, který by tomuto problému mohl zabránit. Vtokový objekt byl pouze namodelován v programu Flow 3D, aby se ukázala jeho funkčnost.

This thesis focuses on setting the range and efficiency of a water ram pump through experimental measurements in a laboratory. The measurements were carried out on three different constructions of water ram pump, each of the designed and assembled by the author of this thesis himself, to find out whether the weight on the pulsating valve has an influence on the water ram pump efficiency. Further on this thesis aims at the comparison of up to now methods of water transport arrangement used at a summer camp and the usage of the water ram pump and its advantages. The principal of water ram pump originates in hydraulic impact that is being precisely described in a great detail as well. On of the chapters even includes the placement manual for the water ram pump and its overall assembly and connexion. Because the presence of floating debris is inevitable, this thesis also deals with the possibility to solve the incoming water impurities by adding an inflow gating to prevent such problem. This inflow gating has only been designed in a Flow 3D programme to introduce the idea and functions.
Determination of the working range and efficiency of the water hammer pump
Keywords: vodní trkač; zpětná klapka; skauting; tábor; vodní ráz; Flow 3D; hydraulic ram pump; check valve; scouting; camp; hydraulic impact; Flow 3D